Comprehensive analysis ofLRRK2in publicly available Parkinson's disease cases and neurologically normal controls - Coro Paisán-Ruı́z; Priti Nath; Nicole Washecka; J. Raphael Gibbs; Andrew Singleton (2008)
Mutation of LRRK2, encoding dardarin, is the most common known genetic cause of Parkinson's disease (PD). The large size of this gene and the relative ease with which the most common mutations can be screened means that although more than 50 LRRK2 screening papers have been published, few have analyzed the entire coding sequence. Furthermore, no comprehensive sequence-based analysis has been performed on control samples. Here, we present sequencing of all coding exons in a series of 275 PD cases and 275 neurologically normal controls and analysis of the LRRK2 locus for whole gene multiplications or deletions. We also present case–control SNP association results using 74 SNPs genotyped across LRRK2. We identified six novel disease-associated missense mutations, including two that altered the same residue of the protein. These data and analysis of previously reported disease-segregating mutations shows that the majority of disease-causing mutations lie in the C-terminal half of the protein. Hum Mutat 29(4), 485–490, 2008. Published 2008, Wiley-Liss, Inc.